Development of DC Microgrid Integrated Electric Vehicle Charging Station With Fuzzy Logic Controller - Mathewos Hadero; Baseem Khan (Frontiers in Energy Research, 2022)
The utilization of the electric vehicles increasing day by day. Further, energy grid infrastructure is not modernized enough to supply the growing demand of electric vehicles. Therefore, it is difficult to fully depend on the energy obtained from grid. As a result, integration of renewable energy (solar), grid supply and energy storage is critical. Therefore, the need of renewable energy powered charging facility with adequate controlling is the present day requirement. This paper proposed the development of a direct current (DC) microgrid for electric vehicle charging stations. This work employs a fuzzy logic controller to optimally integrate a DC microgrid. The maximum operating voltage of this DC microgrid charging station is 500 V. Power flow management using a fuzzy logic controller keeps voltage within the expected range with standard voltage deviation. Further, it improves the response time (1.645 ms). Moreover, the operating costs per year of the proposed system are also being investigated.